SYIRKAH: IMPLEMENTATION OF FRESH WATER FISHING FISHERY (KJA) - J Juliana; Hilda Monoarfa; Muhammad R. L. Putra; Ropi Marlina (STIESA Press, 2020)
The Background in this study is that there is still a lack of understanding among Muslim communities, especially fishery business actors. This study aims to measure the level of understanding and implementation of the syirkah covenants of floating net cage fisheries businesses. This research uses a quantitative descriptive method with a sample of 100 respondents consisting of business people floating net cage fisheries. The sampling technique used is pusposive sampling. The results showed that in general the level of understanding and implementation of the Syrkah contract for freshwater fisheries business operators in Cirata Reservoir in Cianjur Distric was included in the good category, although some indicators in the implementation of the syrkah contract were in the sufficient category.